(untitled) (Research, Society and Development, 2022)
Osteosarcoma is an aggressive malignant mesenchymal neoplasm characterized by the production of osteoid matrix and stromal spindle cells. The present work carried out in the form of a narrative review of the literature aims to identify information about oral osteosarcoma, also emphasizing the importance of early diagnosis of the disease made by the health professional, minimizing its recurrence and metastatic reaction. A search was carried out in the Scielo, Lilacs, Google Scholar and Rsd Journal databases. The investigated literature showed that osteosarcoma is the most common primary malignant tumor of the bone, responsible for 20% of sarcomas, with 5% of these occurring in the maxillofacial region, most often in the mandible. The main signs and symptoms are swelling, pain, paresthesia, tooth mobility and functional limitation. Etiological factors are associated with patient characteristics such as age and sex, as well as genetic factors and pre-existing bone anomalies. The diagnosis is obtained through imaging and histopathological examinations. The best treatment for osteosarcoma is surgical resection of the lesion, minimizing its recurrence and metastatic behavior. Given this reality, the importance of the dentist’s knowledge of the lesion and early diagnosis is reaffirmed.